2014
DOI: 10.1371/journal.pone.0092909
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Combined Clenbuterol and Metoprolol Therapy on Reverse Remodelling during Mechanical Unloading

Abstract: BackgroundClenbuterol (Cl), a β2 agonist, is associated with enhanced myocardial recovery during left ventricular assist device (LVAD) support, and exerts beneficial remodelling effects during mechanical unloading (MU) in rodent heart failure (HF). However, the specific effects of combined Cl+β1 blockade during MU are unknown.Methods and ResultsWe studied the chronic effects (4 weeks) of β2-adrenoceptor (AR) stimulation via Cl (2 mg/kg/day) alone, and in combination with β1-AR blockade using metoprolol ((Met),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Metoprolol, not Clenbuterol, prevented unloading-induced myocardial atrophy, with increased atrophy occurring during combined therapy. Unloading-induced recovery of Ca 2+ transient amplitude, speed of Ca 2+ release and sarcoplasmic reticulum Ca 2+ content was enhanced equally by each monotherapy, but these benefits, together with Clenbuterols enhancement of sarcomeric contraction speed, and unloading-induced recovery of Ca 2+ spark frequency disappeared during combined therapy ( 40 ).…”
Section: Unloading-induced Effects: Good and Badmentioning
confidence: 99%
“…Metoprolol, not Clenbuterol, prevented unloading-induced myocardial atrophy, with increased atrophy occurring during combined therapy. Unloading-induced recovery of Ca 2+ transient amplitude, speed of Ca 2+ release and sarcoplasmic reticulum Ca 2+ content was enhanced equally by each monotherapy, but these benefits, together with Clenbuterols enhancement of sarcomeric contraction speed, and unloading-induced recovery of Ca 2+ spark frequency disappeared during combined therapy ( 40 ).…”
Section: Unloading-induced Effects: Good and Badmentioning
confidence: 99%
“…The β 2 -agonist clenbuterol has been tested in a rat model of mechanical unloading. 4,6,7 Moreover, the β 1 -blocker metoprolol has been investigated in various studies and has been shown to have a positive effect on apoptosis prevention in rat hearts subjected to mechanical unloading. 7,8 For treating cases of heart failure, the nonselective β-blocker carvedilol is a representative drug that has cardioprotective effects similar to those of metoprolol.…”
mentioning
confidence: 99%
“…This indicates that β-blocker, alone, likely does not have any effects on promoting reverse cardiac remodeling [ 33 ], emphasizing that much of unloading is due to LVAD. Nevertheless, the combination of LVAD and β-blocker has attracted more and more interest due to its exciting effects on improving cardiac function [ 19 , 34 ]. However, the mechanism and pathway of β-blocker in the therapy is still unclear.…”
Section: Discussionmentioning
confidence: 99%